Caracterização Bioquímica do Nematóide das Galhas (meloidogyne spp.) Caracterização Bioquímica do Nematóide das Galhas (meloidogyne spp.) Em lavouras de Arroz Irrigado na Região Central do Rio Grande do Sul - Steffen, Ricardo Bemfica (2007)
Twenty one populations of the root-knot nematode (Meloidogynespp.) from eight site located in districts of the Central area of Rio Grandedo Sul State, were biochemical characterized through the esteraseisoenzyme. Sampling was performed in areas with chlorotic plants,exhibiting deformated radicular systems typical symptoms of root-knotnematode attack. Esterase isoenzyme, identified in all the sites sampledthe phenotype esterase VS1 (Rm 0,70), typical of M. graminicola.